The Significance of Main Constructs of Theory of Planned Behavior in Recent Information Security Policy Compliance Behavior Study: A Comparison among Top Three Behavioral Theories - Nasir, Akhyari; Ruzaini, Abdullah Arshah; Mohd Rashid, Ab Hamid (Science Publishing Corporation, 2018)
For a decade since year of 2000 until 2010, Theory of Planned Behavior [TPB] and its main construct of Attitude, Normative belief and Self-efficacy have been considered as a significant theory and factors in the area ISP compliance behaviour study. However, there are still some questions exist particularly on to what extent this theory is significant in recent studies compared to other competing theories. This paper presents a comparison on main constructs of top three behavioral theories in predicting and explaining the recent ISP compliance studies. The studies on ISP compliance published from 2010 until 2016 will be used to analyse the significance of this TPB compared to General Deterrence Theory [GDT] and Protection Motivation Theory [PMT]. Criteria of comparisons are based on the significance of main constructs towards dependent variable and the comprehensiveness of a theory’s main constructs usage in a research model from the selected studies. The results have confirmed that TPB is still relevant as the most significant in the area of ISP compliance study and its main constructs are the strongest predictors of dependent variables in most of ISP compliance models compare to GDT and PMT. This paper provides a clear status on the significance of TPB and its main constructs of Attitude, Normative belief and Self-efficacy in predicting and explaining ISP compliance behavior in recent studies. It could be used by academicians as references for statistical evidences on the comparison of the top behavioral theories.